Actin cortical cytoskeleton and cell wall synthesis in regenerating protoplasts of the Saccharomyces cerevisiae actin mutant DBY 1693 - Kopecká, Marie; Gabriel, Miroslav (Microbiology (Reading, England), 1995)
The relationship between the actin cytoskeleton and cell wall synthesis was studied by light and electron microscopy in protoplasts of Saccharomyces cerevisiae DBY 1693 containing the act1-1 allele. Since protoplasting also disturbs the actin cytoskeleton, these mutant protoplasts had a double error in their actin cytoskeletons. In the period between the onset of wall synthesis and completion of the wall, protoplasts grown at the permissive temperature showed an even distribution of actin patches all over the surface on which a new cell wall was being synthesized. After wall completion, actin patches partially disappeared, but then re-appeared, accumulated in growth regions at the start of polarized growth. This was compared with the pattern of actin patches observed in intact temperature-sensitive actin mutant cells cultivated at the permissive temperature. Electron microscopy of freeze-etched replicas revealed finger-like invaginations of the plasma membrane in both the actin mutant cells and their protoplasts. These structures showed a very similar distribution to the actin patches detected by rhodamine phalloidin staining in the fluorescence microscope. A hypothesis is presented, explaining the role of actin patches/finger-like invaginations of the plasma membrane in the synthesis of beta-(1-->3)-D-glucan wall microfibrils in yeast cells.
Keywords: aktiny; Saccharomyces cerevisiae; Protoplasts; Models, Molecular; protoplasty; teplota; buněčná stěna; leptání mrazem; Actins; Freeze Etching; Cell Wall; cytoskelet; Temperature; fungální proteiny; molekulární modely; Cytoskeleton; Fungal Proteins